2013
DOI: 10.1111/apps.12009
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Job-Seeking Behavior of the Unemployed: The Effect of Individual Differences in Justice Sensitivity

Abstract: This study examines the effect of justice sensitivity on the life satisfaction and job‐seeking behavior of unemployed individuals and considers the likelihood of experiencing long‐term unemployment. We focus on two facets of dispositional justice sensitivity that reflect individual differences in perception and reactions to perpetrating injustice against others (perpetrator sensitivity) or suffering from the injustice of others as an innocent victim (victim sensitivity). We hypothesised that the negative effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…The scales included 3 items each—Cronbach’s α: .66 (extroversion), .51 (agreeableness), .62 (conscientiousness), .60 (neuroticism), and .63 (openness)—and were answered using a 7-point scale ranging from does not apply to does apply . Given the extremely short length of the scales, a relatively low internal reliability is considered acceptable among individual differences researchers (Rammstedt, Spinath, Richter, & Schupp, 2013; Stavrova, Schlösser, & Baumert, 2014). We also included participants’ age and gender (men were coded as 1 and women as 0) as control variables.…”
Section: Methodsmentioning
confidence: 99%
“…The scales included 3 items each—Cronbach’s α: .66 (extroversion), .51 (agreeableness), .62 (conscientiousness), .60 (neuroticism), and .63 (openness)—and were answered using a 7-point scale ranging from does not apply to does apply . Given the extremely short length of the scales, a relatively low internal reliability is considered acceptable among individual differences researchers (Rammstedt, Spinath, Richter, & Schupp, 2013; Stavrova, Schlösser, & Baumert, 2014). We also included participants’ age and gender (men were coded as 1 and women as 0) as control variables.…”
Section: Methodsmentioning
confidence: 99%
“…It has demonstrated that job satisfaction has both direct and indirect effects on organizations. High levels of job satisfaction are related with lower absenteeism, higher productivity or performance, higher staff retention, higher engagement and commitment, higher life satisfaction and motivation (Iliescu, Ispas, Sulea, & Ilie, 2015;Nyberg & Ployhart, 2013;O'Keefe, 2014;Stavrova, Schlosser, & Baumert, 2014).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Specifically, while on the one hand victim sensitivity embraces a self-focused justice concern, observer, beneficiary, and perpetrator sensitivity involve a genuine concern for others and reflect an otherfocused justice concern (Baumert et al, 2012). For this reason, measurement tools assessing justice sensitivity often combine scores from observer, beneficiary, and perpetrator sensitivity scales into a single index (i.e., JS-Others), to be contrasted with the index of victim sensitivity (i.e., JS-Victim; Fetchenhauer & Huang, 2004;Lotz, Schlösser, Cain, & Fetchenhauer, 2013;Stavrova, Schlösser, & Baumert, 2014). Interestingly, research conducted with adult samples has shown that JS-Victim and JS-Others are differently associated with attitudes and behavioral outcomes.…”
Section: Different Facets Of Justice Sensitivity and Behavioral Outcomesmentioning
confidence: 99%